Physico-chemical characteristics of microcrystalline cellulose from switchgrass (Panicum virgatum L.) obtained in the presence of a solid catalyst - T. V. Tkachenko; O. O. Haidai; D. S. Kamenskyh; Y. V. Sheludko; O. V. Pavliuk; V. O. Yevdokymenko (Хімія, фізика та технологія поверхні, 2024)
The main idea of this work is the investigation of structural and morphological characteristics of microcrystalline cellulose with switchgrass (Panicum virgatum L.) by the method of organo-solvent cooking with the addition of various brands of ion-exchange resins instead of sulfuric acid. A sulfonated copolymer of styrene and divinyl benzene with two functional groups per ring - Purolite CT-275 and a sulfonated copolymer based on tetrafluoroethylene - Nafion NR-50 were chosen as initial ion exchange resins. Air-dry switchgrass (Panicum virgatum L.), a technical culture, was used for the research. Microcrystalline cellulose (MCC) was obtained from it by the method of organo-solvent cooking with the addition of a solid catalyst. Using the methods of XRD, FTIR-ATR, AFM, TGA and DSC, the structure and morphology of MCC were studied. It is found that the use of ion-exchange resins in the organo-solvent method of obtaining MCC in a batch reactor requires the use of protective covers for the catalyst to avoid its mechanical damage. It has been found that only sulfonated copolymers based on tetrafluoroethylene are stable in the cooking solution, in contrast to sulfonated copolymers of styrene and divinylbenzene, and allow obtaining MCC from millet with a yield of 53 % versus 40 % for the classical method and a degree of polymerization of 440 versus 578, respectively. Due to the destruction of amorphous binders in the MCC’s from switchgrass (Panicum virgatum L.), regardless of the conditions of its production, we observe further ordering of the structure of the obtained MCC which is expressed in narrower and more intense peaks in the range 2? = 22–23°. The FTIR-ATR method showed that the obtained MCC has functional groups similar to commercial M-1021. The AFM method showed that MCC has a globular and wavy relief. Surface roughness with globular relief is 12.6 nm.